Novel linezolid resistance plasmids in Enterococcus from food animals in the USA. (1st October 2018) - Tyson, Gregory H; Sabo, Jonathan L; Hoffmann, Maria; Hsu, Chih-Hao; Mukherjee, Sampa; Hernandez, Jacqueline; Tillman, Glenn; Wasilenko, Jamie L; Haro, Jovita; Simmons, Mustafa; Wilson Egbe, Wanda; White, Patricia L; et al.
Abstract: Objectives: To sequence the genomes and determine the genetic mechanisms for linezolid resistance identified in three strains of Enterococcus isolated from cattle and swine caecal contents as part of the US National Antimicrobial Resistance Monitoring System (NARMS) surveillance programme. Methods: Broth microdilution was used for in vitro antimicrobial susceptibility testing to assess linezolid resistance. Resistance mechanisms and plasmid types were identified from data generated by WGS on Illumina ® and PacBio ® platforms. Conjugation experiments were performed to determine whether identified mechanisms were transmissible. Results: Linezolid resistance plasmids containing optrA were identified in two Enterococcus faecalis isolates and one Enterococcus faecium . The E. faecium isolate also carried the linezolid resistance gene cfr on the same plasmid as optrA . The linezolid resistance plasmids had various combinations of additional resistance genes conferring resistance to phenicols ( fexA ), aminoglycosides [ spc and aph(3′)-III ] and macrolides [ erm (A) and erm (B)]. One of the plasmids was confirmed to be transmissible by conjugation, resulting in linezolid resistance in the transconjugant. Conclusions: To the best of our knowledge, this is the first identification of linezolid resistance in the USA in bacteria isolated from food animals. The oxazolidinone class of antibiotics is not used in food animals in the USA, but the genes responsible for resistance were identified on plasmids with other resistance markers, indicating that there may be co-selection for these plasmids due to the use of different antimicrobials. The transmissibility of one of the plasmids demonstrated the potential for linezolid resistance to spread horizontally. Additional surveillance is necessary to determine whether similar plasmids are present in human strains of Enterococcus .